THINK-PAIR-SHARE STRATEGY TO IMPROVE THE STUDENTS’ SPEAKING ABILITY - ST Marhana Rullu; Rusdayanti Abdullah (English Education Study Program, 2020)
This research aims to determine whether using Think-Pair-Share strategy can improve speaking ability of students in SMP Negeri 3 Luwuk. It applied a quasi-experimental research using non-equivalent design. The research populations were the eighth grade of students in SMP Negeri 3 Luwuk and the sample of the research were class VIII A as the experimental class and class VIII B as the control class. The research instrument used a test which was divided into two parts, namely pre-test and post-test. Data were analyzed statistically. After being analyzed, the result showed that there was a significant improvement in students’ speaking ability in using Think-Pair-Share strategy. In the experimental class, the mean score in pre-test was 46.3 while in the post-test was 81.2. In the control class, the mean score in pre-test was 45.8 while in the post test was 61.6. From the calculation in t-counted was higher that t-table. The result in t-counted was 14.984 while the t-table in the degree of significance 0.05 was 1.667. If the value of t-counted > t-table, it means that Ha is accepted and HΟ is rejected. In other words, the alternative hypothesis is proven. From the result of the research showed that there was a significant improvement in students’ speaking ability in using Think-Pair-Share strategy.